Multi-finger Haptic Interaction - Galiana, Ignacio; Ferre, Manuel; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Multi-finger Haptic Interaction presents a panorama of technologies and methods for multi-finger haptic interaction, together with an analysis of the benefits and implications of adding multiple-fingers to haptic applications. Research topics covered include: design and control of advanced haptic devices; multi-contact point simulation algorithms; interaction techniques and implications in human perception when interacting with multiple fingers. These multi-disciplinary results are integrated into applications such as medical simulators for training manual skills, simulators for virtual prototyping and precise manipulations in remote environments. Multi-finger Haptic Interaction presents the current and potential applications that can be developed with these systems, and details the systems$1 (Bcomplexity. The research is focused on enhancing haptic interaction by providing multiple contact points to the user. This state-of-the-art volume is oriented towards researchers who are involved in haptic device design, rendering methods and perception studies, as well as readers from different disciplines who are interested in applying multi-finger haptic technologies and methods to their field of interest.s
Foreword -- Introduction -- Multi-Finger Grasps in a Dynamic Environment -- 3D Interaction Techniques for Bimanual Haptics in Virtual Environments -- Modular Multi-Finger Haptic Device: Mechanical Design, Controller and Applications -- HIRO: Multi-Fingered Haptic Interface Robot and Its Medical Application Systems -- Two-Handed Multi-Finger String-Based Haptic Interface SPIDAR-8.
Keywords: Computer science; Computer simulation; Engineering design; Computer Science; User Interfaces and Human Computer Interaction; Simulation and Modeling; Control, Robotics, Mechatronics; Engineering Design; Numerical and Computational Physics